Blended Learning Development In Islamic Religious Education Lessons Make Use of Web and Android - Suhada, H; Nulhakim, Lukman; Sudarto, Ferry; Kristiadi, Dedy Prasetya (International Journal for Educational and Vocational Studies, 2019)
The study of Islamic religious education in the era of industrial revolution 4.0 requires teaching methods which involve the role of information and communication technology in order to produce the expected quality. students cannot participate in learning maximally which has an impact on the quality of learning.The independence of learning is the goal of this study because to be able to absorb the knowledge of Islamic education it requires a great deal of motivation both theory and practice. Blended learning is a learning model which combines study in the classroom  transitional which combines conventional learning with e-learning while increasing student independence. In its implementation, blended learning allows students to get explanations from lecturers in class, then proceed with collaboration in groups and present assignments online by video conference presentations made separately by each group member. The video then uploaded to the e-learning system by group members and it can be seen online by the class participants according to the lesson schedule, to be given a score and description of the presentation to each group member online. Blended learning represents new method  to create learning experiences that can provide the right learning at the right time and in the right place for each and every individual and bringing groups of learners together through different cultures.